휘핑계수-수중폭발 가스구체 압력파 크기의 척도 - 권정일(Jeong-II Kwon); 정정훈(Jung-Hoon Chung); 이상갑(Sang-Gab Lee) (大韓造船學會 論文集, 2005)
A new novel Whipping Factor is proposed as a measure of the ship damage potential due to an underwater explosion bubble pulse. The factor was derived from the relationships among the charge weight, its depth and the fluid acceleration due to pulsating gas bubble. From the whipping response analyses for three uniform Timoshenko beams with similar characteristics of real naval surface ships, we have confirmed the maximum bending moment responses of beams due to whipping are almost same if the applied whipping factor is constant regardless of the charge weights and depths, which could validate the proposed whipping factor.